Development of national food culture in medieval Serbia - Ђуровић, Младенка; Божић, Александар; Борковић, Милана; Тошић, Теодора (The Business of Tourism, 2023)
Summary: The way of eating in a certain historical period in a country can be an interesting indicator of the economic, agricultural and social climate, but also of various influences from the environment. Dining in the Middle Ages was conditioned by social and material status. The way of life in the city and the village differed, and this can easily be established on the basis of their tables. Peasants had to grow their own livestock, grains, fruits and vegetables, while the privileged bought them at the markets or imported them from abroad. The limited availability of products that can be used to prepare meals made the people in the countryside more appreciative of everything they produced, and wasting food was almost unthinkable. The study of food production and methods of preparation and consumption has become interesting to science only in the last few decades - studies of other sociological activities took precedence. The table is a precise indicator of all life circumstances: social status, joys and sorrows, traditions or rituals. In addition, the geographical position of Serbia on the Balkan Peninsula, where the roads between Europe and Asia cross, has resulted in the mixing of different cultures, and thus has influenced the culture of food. The medieval population of Serbia inhabited geographically diverse areas, there were frequent migrations, wars, looting and robbery. Serbia was often affected by droughts and diseases, but marriages were also made between noble families. All that left its mark on Serbian cuisine. The meeting of Oriental and Central European cultures brought variety in the number of foods, their processing and processing, storage methods and customs, as well as table manners. The beginnings of the national cuisine of the Serbs are linked to the Nemanjić dynasty. There are numerous historical sources about the development of culinary culture, and reliable testimonies are church charters and similar sources.